Effects of nano-composite adsorbents on the growth performance, serum biochemistry, and organ weights of broilers fed with aflatoxin-contaminated feed - Saminathan, Mookiah; Selamat, Jinap; Pirouz, Atena Abbasi; Abdullah, Norhani; Idrus, Zulkifli (MDPI, 2018)
The exploration of feed mycotoxin adsorbents to mitigate the adverse effects of mycotoxins on animals has received increasing attention over the last decade. The present study was conducted to assess the efficacy of nano-composite magnetic graphene oxide with chitosan (MGO-CTS) adsorbents against feed contaminated with ~20 ng/g (ppb) aflatoxin (AF). A total of three hundred 1-day-old chicks were randomly distributed into six dietary treatment groups, as follows: basal diet (broilers fed a diet with neither AF nor MGO-CTS added, T1), basal diet + 0.25% MGO-CTS (T2), basal diet + 0.50% MGO-CTS (T3), AF diet + 0.25% MGO-CTS (T4), AF diet + 0.50% MGO-CTS (T5), and AF diet (T6). The two inclusion levels (0.25 and 0.50%) of MGO-CTS significantly (p < 0.05) improved the growth performances and feed conversion ratios of the AF-treated chicks at 1–35 days of age, and the impact was more pronounced for 0.5% MGO-CTS. The AF intake markedly increased the relative weights of the liver and kidney, resulting in significant alterations in the serum biochemical parameters, such as albumins, alkaline phosphatase, and SGPT/alanine (ALT), at 35 days of age. However, the chickens fed 0.5% MGO-CTS with AF diets had apparent recovery or restoration of AF-induced organ lesions and aberrant serum profiles. A significant (p < 0.05) reduction in the total AFs was observed in the gastrointestinal tracts of the chickens fed 0.25% or 0.50% adsorbent in combination with AF feed (T4 and T5), with decreases of 28.9% and 53.5%, respectively, compared with that in the chickens fed an AF-contaminated diet (T6). The results of the study indicated that a higher concentration of MGO-CTS (0.50%) was effective in improving the overall performance of broiler chickens by preventing the adverse effects associated with aflatoxicosis.